Moving from pedagogy to andragogy / Misyana Susanti Husin and Jahjaiton Arsad - Husin, Misyana Susanti; Arsad, Jahjaiton (2004)
Learners of higher leaming institutions are young adults who are uniquely different in characteristics, expectations and motivational factors in learning. In many ways, the pedagogical model, "the art and science of teaching children", used in the higher learning context, make leamers become passive and dependent aside from lacking skills necessary for higher education studies. This paper aims at discussing the rationale, constraints, potentials and constructive key implications of incorporating andragogical model, "the art and science of teaching adults", in higher education.